Morpho-taxonomic description of cypsela features in two genera of tribe Mutisieae (Asteraceae) - Dibyendu Talukdar, Tulika Talukdar, (Current Botany, 2015)
Micro-morphological, macro-morphological, anatomical features of cypsela features of two genera Leibnitzia nepalensis (Kuntze)Kitam. And Onoseris sagittatusÂ Rusby of tribe Mutisieae of family Asteraceae have been investigated by using light and scanning electron microscopy. Cypsela homomorphic and carpopodium symmetric in both genera. Cypsela narrow elliptic in cross section, ribbed. However, in Leibnitzia, cypsela slightly curved with ill-developed ribs; hairs sparsely distributed; stylopodium ill-developed; carpopodium diameter is comparable to the base of the cypsela; insertion of cypsela oblique;Â pappus basally united; cypsela elliptic in T.S.; epicarpic cuticle absent; mesocarpic parenchyma absent; secretory ducts in each cotyledon equal in size. Contrastingly, in Onoseris, cypsela straight; ribs prominent; hairs densely distributed; stylopodium well-developed; diameter of carpopodium lesser than the base of the cypsela; insertion of cypsela straight;Â pappus basally free; cypsela angular in T.S.; epicarpic cuticle present; mesocarpic parenchyma present; secretory ducts in each cotyledon unequal in size.